The relationship between prenatal testosterone and developmental stuttering in boys - Dönmez, Yunus Emre; Özcan, Özlem; Bilgiç, Ayhan; Miniksar, Dilşad Yıldız (The Turkish Journal of Pediatrics, 2019)
Stuttering is a multi-factorial speech disorder characterized by various dysfluencies in the beginning and/or smooth flow of speech. Its incidence is about 1% in the general population, with 80% of stuttering cases seen in children aged three to eight years. The etiology of developmental stuttering has not been precisely explained. Several researchers report that neurological factors, especially atypical lateralization of the speech and language processes, play an important role in the etiology of stuttering. Various hypotheses suggest that prenatal testosterone causes atypical hemispheric lateralization. The aim of this study was to investigate the role of prenatal testosterone in the etiology of developmental stuttering by the use of the ratio of secondand fourth-digit lengths (2D:4D). Totally 133 boys (49 boys who stutter and 84 boys who do not stutter) were included in the study. The age range of children participating in the study was determined as 2-12 years. In the comparative evaluation conducted between the stuttering group and the control group in terms of their right 2D:4D and left 2D:4D ratios, it was found that the left 2D:4D ratio of the patients was significantly higher than that of the control group. We are of the opinion that prenatal testosterone may play a role in the etiology of developmental stuttering. The present study is the first study in the literature to reveal a relationship between prenatal testosterone and developmental stuttering.